2014
DOI: 10.2218/jls.v1i1.785
|View full text |Cite
|
Sign up to set email alerts
|

“Mucientes Chert” in the Northern Iberian Plateau (Spain)

Abstract: Abstract:The so-called "Mucientes chert" is a variety that appears in the central area of the Iberian North Plateau, in the Duero Basin. It is widely known in the geological and archaeological literature and its use for knapping was especially important in Prehistory. From a macroscopic point of view it is a nodular chert, with white and very porous cortex, and brown to blackish or beige colour in the inner part.In this work we carried out a more accurate petrographic, mineralogical and chemical characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Geological study and recent surveys developed for the study of the Côa Valley sites have also revealed the potential of Miocene age lacustrine deposits containing flint (evaporitic silcrete) in the Douro and Tagus basin and the existence of Palaeogene pedogenic and groundwater silcretes (Armenteros Armenteros 1986;Aubry et al 2012;Blanco et al 2008;Fuertes Prieto et al 2014) (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
“…Geological study and recent surveys developed for the study of the Côa Valley sites have also revealed the potential of Miocene age lacustrine deposits containing flint (evaporitic silcrete) in the Douro and Tagus basin and the existence of Palaeogene pedogenic and groundwater silcretes (Armenteros Armenteros 1986;Aubry et al 2012;Blanco et al 2008;Fuertes Prieto et al 2014) (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
“…(Figure 2). Samples belonging to this collection have been published in several papers such as those from Vegamián Formation (Herrero-Alonso et al 2016), Escalada Formation (Fuertes- and Mucientes locality (Fuertes- Prieto et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, attempts have been made in recent years to characterise the types of chert that outcrop in different Iberian regions and were probably most used by prehistoric communities. Some examples in the Spanish literature include studies from the Baetic System (Lozano et al 2010;Morgado et al 2011), Madrid Basin (Bustillo and Pérez-Jiménez 2005), Northern subplateau (Fuertes-Prieto et al 2014), Cantabrian Mountains ) and the Basque-Cantabrian Basin and Navarran Pyrenees (Tarriño et al 2007(Tarriño et al , 2015. The current situation is quite different in the Ebro Basin, where many geological formations containing siliceous rocks are attested but these are not well characterized.…”
Section: Introductionmentioning
confidence: 99%